2018
DOI: 10.21037/ajo.2018.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological predictors of positive rigid bronchoscopy findings in children with suspected tracheobronchial foreign body aspiration

Abstract: Background: Tracheobronchial foreign body aspiration (TFBA) is common in young children and is associated with potentially significant morbidity, and sometimes mortality. Although rigid bronchoscopy (RB) is often needed for definitive diagnosis, it can be associated with intra-operative and long-term risks. Methods: Hospital records of patients under 18 years of age who underwent RB for suspected TFBA between November 2010 and May 2016 were retrospectively reviewed. Data extracted include age, gender and date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This is comparable with previous studies. 31 , 32 Conversely, Kwok et al 33 reported the absence of a significant difference for children with and without FBA and a clinical history of aspiration, auscultation, and radiographic abnormalities. Though their study was limited by a small sample size (43 participants), it was valuable to evaluate children with suspected FBA for viral respiratory infection especially in infants younger than 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with previous studies. 31 , 32 Conversely, Kwok et al 33 reported the absence of a significant difference for children with and without FBA and a clinical history of aspiration, auscultation, and radiographic abnormalities. Though their study was limited by a small sample size (43 participants), it was valuable to evaluate children with suspected FBA for viral respiratory infection especially in infants younger than 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of foreign bodies is certainly challenging to the otolaryngologist because of the variety of objects swallowed or aspirated. The technical difficulties involved and complication which may occur due to the lack of knowledge about the foreign body complication of layman and unavailability of specialists are the main reason for life threatening morbidity and mortality [4].…”
Section: Introductionmentioning
confidence: 99%